A comparison of electrical performance analysis between nanoscale double-gate and gate-all-around nanowire mosfet - Kosmani, Nor Fareza (2020)
The Double-Gate and Gate-all-Around are said to be the promising candidates to pursue Complementary-Metal-Oxide Semiconductor scaling. When the device is scaled down, several problems arise such as the short-channel effect, excessive transistor gate leakage and power consumption. The purpose of this simulation work is to compare the performance of Double-Gate and Gate-All-Around and study the effect of scaling physical dimension on devices performance using Atlas Silvaco. It is found that when the gate length approaches 30 nm, the subthreshold slope increases for both devices while the threshold voltage is decreases. Futhermore, the threshold voltage will decrease with the decreasing of gate oxide thickness whilst increasing the silicon body thickness for both devices. Even though higher doping concentration is good for suppressing short channel effects, the lower doping concentration is desirable as both devices inhibit higher on-state currents. Gate-AllAround has greater value of current ratio compared to Double-Gate with 99.99% difference for low, light and heavy doping concentration. The gate dielectric materials play a significant role in the high performances of nanoscale devices. Different types of high dielectric constant material are used in order to study its influence towards Double-Gate and Gate-All-Around. The materials chosen in this study are Silicon Nitride, Aluminium Oxide, Zirconium Oxide and Hafnium Oxide. It can be observed that when approaching a higher value of dielectric constant, the on current, on-to-off current ratio and threshold voltage will increase while the subthreshold slope and off current will decrease. Hafnium Oxide shows the best performance compared to other simulated dielectric materials by having an improvement of leakage current with 98.64% and 73.85% when gate length approaching 30 nm for Double-Gate and Gate-All-Around respectively. Overall, Gate-All-Around offers a better continuous scaling down process compare to Double-Gate due to its efficient gate control, high current ratio, better short channel effect and subthreshold slope characteristics.